Animation Media for Elementary School Students: Efforts to Improve Numeracy Skills - Elya Rosalina; Riduan Febriandi (Postgraduate, University of Mataram, 2025)
Mathematics is essential for developing students’ problem-solving skills, as many real-life issues can be addressed through mathematical models. However, the 2018 PISA survey ranked Indonesia 72nd out of 78 countries in numeracy, with an average score of 379. In schools, mathematics is often taught using fewer engaging methods, which may lower students’ interest and performance. Video-based media is considered effective for elementary students, offering a more enjoyable learning experience. This study aims to improve the numeracy skills of Grade 3 students at SDN 14 Lubuklinggau using animated video media featuring the character Loomie. The research employed classroom action research (CAR) following the Kemmis and Taggart model, conducted in two cycles: planning, action, observation, and reflection. The topic was 2D shapes. The pre-test average score was 13.5. In Cycle 1, the post-test average rose to 63, showing improvement but still below expectations. In Cycle 2, the average increased significantly to 80. These findings indicate that animated video media can effectively enhance students’ numeracy skills. Thus, incorporating animation into mathematics instruction can be a promising strategy to improve student engagement and academic outcomes, especially in early grades.